Extracellular Vesicles Derived From Murine Cementoblasts Possess the Potential to Increase Receptor Activator of Nuclear Factor-κB Ligand-Induced Osteoclastogenesis - Sato, Rei; Maruyama, Kentaro; Nemoto, Eiji; Sakisaka, Yukihiko; Suzuki, Shigeki; Li, Jiajun; Numazaki, Kento; Tada, Hiroyuki; Yamada, Satoru (Frontiers in Physiology, 2022)
Cementum resorption, unlike bone resorption, is clinically known to occur only with limited pathological stimuli, such as trauma, orthodontic forces, and large apical periodontitis; however, the molecular mechanisms that control osteoclast formation on the cementum surface remain unclear. In this study, we focused on extracellular vesicles (EVs) secreted by cementoblasts and analyzed their effects on osteoclast differentiation. EVs were extracted from the conditioned medium (CM) of the mouse cementoblast cell line OCCM-30. Transmission electron microscopy (TEM) analysis confirmed the presence of EVs with a diameter of approximately 50–200 nm. The effect of the EVs on osteoclast differentiation was examined using the mouse osteoclast progenitor cell line RAW 264.7 with recombinant receptor activator of nuclear factor (NF)-κB ligand (rRANKL) stimulation. EVs enhanced the formation of tartrate-resistant acid phosphatase (TRAP) activity-positive cells upon rRANKL stimulation. EVs also enhanced the induction of osteoclast-associated gene and protein expression in this condition, as determined by real-time PCR and Western blotting, respectively. On the other hand, no enhancing effect of EVs was observed without rRANKL stimulation. A Western blot analysis revealed no expression of receptor activator of NF-κB ligand (RANKL) in EVs themselves. The effect on rRANKL-induced osteoclast differentiation was examined using the CM of cementoblasts in terms of TRAP activity-positive cell formation and osteoclast-associated gene expression. The conditioned medium partly inhibited rRANKL-induced osteoclast differentiation and almost completely suppressed its enhancing effect by EVs. These results indicate that cementoblasts secreted EVs, which enhanced RANKL-induced osteoclast differentiation, and simultaneously produced soluble factors that neutralized this enhancing effect of EVs, implicating this balance in the regulation of cementum absorption. A more detailed understanding of this crosstalk between cementoblasts and osteoclasts will contribute to the development of new therapies for pathological root resorption.